Global employment and social trends. Issue 1 (January 2017) - Kühn, Stefan; Milasi, Santo; Horne, Richard; Yoon, Sheena
Abstract: Against the backdrop of a rather disappointing economic performance in 2016 and the below‐trend outlook for 2017, Chapter 1 assesses the ability of the economy to (i) generate a sufficient number of jobs, (ii) improve the quality of employment for those with a job, and (iii) ensure that the gains of growth are shared in an inclusive manner. The chapter also discusses the policy efforts needed to overcome structural impediments to growth, including inequality.